2017
DOI: 10.1186/s12913-017-2525-4
|View full text |Cite
|
Sign up to set email alerts
|

Social and economic value of Portuguese community pharmacies in health care

Abstract: BackgroundCommunity pharmacies are major contributors to health care systems across the world. Several studies have been conducted to evaluate community pharmacies services in health care. The purpose of this study was to estimate the social and economic benefits of current and potential future community pharmacies services provided by pharmacists in health care in Portugal.MethodsThe social and economic value of community pharmacies services was estimated through a decision-model. Model inputs included effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
(52 reference statements)
0
19
0
Order By: Relevance
“…Community pharmacists (CPs) represent a conspicuous part of pharmacist fraternity, who are equally trained, thoroughly skilled, and well qualified. Recently in developed countries, CPs have been involved in direct patient care for health promotion and medication management services in various chronic diseases, such as hypertension, diabetes, and asthma. 11 The expanded role of CPs in patient’s education, adherence support, and medication therapy management becomes more important as asthma involves a chronic cycle, specialized devices, periodic assessments, self-monitoring, and an individualized therapeutic plan, and CPs have vast potential to provide these interventions 12,13…”
Section: Introductionmentioning
confidence: 99%
“…Community pharmacists (CPs) represent a conspicuous part of pharmacist fraternity, who are equally trained, thoroughly skilled, and well qualified. Recently in developed countries, CPs have been involved in direct patient care for health promotion and medication management services in various chronic diseases, such as hypertension, diabetes, and asthma. 11 The expanded role of CPs in patient’s education, adherence support, and medication therapy management becomes more important as asthma involves a chronic cycle, specialized devices, periodic assessments, self-monitoring, and an individualized therapeutic plan, and CPs have vast potential to provide these interventions 12,13…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the CPS have expanded in different settings into the health systems [ 8 10 ]. In Brazil it would not be different, because CPS have been implemented in the Brazilian Health System (SUS) in the last ten years [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…blood glucose measurements A ssessment: Drug Related Problems (DRPs) P lan: e.g. referral to physician, patient education and informationObservational - process indicators of Diabetes Management Program (2004–2008)356 in 2005379 in 20081294 in 2005Pilger D (2007) [37]Screening of individuals at risk of diabetesScreening patients with > 45 years and another risk factor for diabetes: blood glucose measurement and referral to physician as per intervention protocolDescriptive cross-sectional study (2005)8229Horta MR (2010) [38]Screening of uncontrolled diabetic patientsScreening patients on diabetes medications: blood glucose measurement, reinforcing adherence and self-monitoring, and referral to physician as per intervention protocolDescriptive cross-sectional evaluation of nationwide campaign (2007)7237719ES Research (2009) [39]Screening of uncontrolled diabetic patientsScreening patients on diabetes medications: blood glucose measurement, reinforcing adherence and self-monitoring, and referral to physician as per intervention protocolEconomic evaluation of nationwide campaign (2007)7237719Jacinto I (2016) [48]Screening of individuals at risk of diabetesPromoting FINDRISK test to all adult non-diabetic individuals (except pregnant women) and healthy lifestyle habits, referral to physician if score > 15 points.Descriptive cross-sectional evaluation of regional campaign (2015)2257007Paulino E (2017) [49]Screening of individuals at risk of diabetes and diabetes management1) Promoting FINDRISK test to all individuals and referral of high-risk patients to pharmacy services, to physician or re-evaluation in 1 year, as appropriate2) Follow-up of diabetic patients with assessment of health problems, reinforcing adherence, referral to other providers or to pharmacy consultationsDescriptive cross-sectional evaluation of regional initiative (2016/17)1) 262) 311) 1962) 106Félix J 2017 [52]Screening of individuals at risk, screening of uncontrolled diabetic patients, and diabetes managementIncludes the interventions of studies [31, 32, 35, 38] (Economic study partially based on data of these studies) Economic evaluation (decision-model)NA (model-based)NA (model-based) NR not reported, NA not applicable…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, Felix et al estimated the social and economic benefits of Portuguese pharmacy public health interventions based on volume data of services provided in the last 25 years [ 52 ]. The annual economic value of promoting adherence, although not limited to diabetes, was estimated at 237.6 million euros, and that of direct interventions in diabetes was estimated at 32.9 million euros (15.8% of all pharmacy-based disease interventions).…”
Section: Resultsmentioning
confidence: 99%